2020
DOI: 10.3389/fpubh.2020.00418
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Gender-Based Differences in COVID-19

Abstract: The novel coronavirus disease (COVID-19) has become a global health crisis since its first appearance in Wuhan, China. Current epidemiological studies suggest that COVID-19 affects older patients with multiple comorbidities, such as hypertension, obesity, and chronic lung diseases. The differences in the incidence and severity of COVID-19 are likely to be multifaceted, depending on various biological, social, and economical factors. Specifically, the socioeconomic differences and psychological impact of COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
234
6
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(292 citation statements)
references
References 64 publications
16
234
6
7
Order By: Relevance
“…We noted that males were more likely to be confirmed with COVID-19 infection, which is frequently reported elsewhere. 6 8 9 While some studies indicate that male sex is also associated with severe disease course and death, 6 10 severe cases were rare and poorly documented among the travelers included in the current study, making them impossible to be included in the current analysis. Other studies report old age to be as another predominant factor of COVID-19 infection.…”
Section: Discussionmentioning
confidence: 95%
“…We noted that males were more likely to be confirmed with COVID-19 infection, which is frequently reported elsewhere. 6 8 9 While some studies indicate that male sex is also associated with severe disease course and death, 6 10 severe cases were rare and poorly documented among the travelers included in the current study, making them impossible to be included in the current analysis. Other studies report old age to be as another predominant factor of COVID-19 infection.…”
Section: Discussionmentioning
confidence: 95%
“…The importance of influenza vaccination is well established both for the general population, and especially among patients with prior ASCVD who may benefit from it for secondary prevention [6] . There are known racial disparities in both diagnosis and treatment of ASCVD [12] , [13] , [14] . We also found that there may be similar disparities in receiving a flu vaccine whereby Blacks and Hispanics with ASCVD were less likely to receive a flu vaccine compared to Whites.…”
Section: Discussionmentioning
confidence: 99%
“…40 Socioeconomic status and educational status of the mother and child should also be assessed, as causes of adverse outcomes can be social as well as biological. Additionally, COVID-19 infection appears to be more common and severe in racial and ethnic minorities in the U.S. 41 Moreover, preexisting conditions increase the severity of COVID-19 infection, which may have implications for transmission and neonatal outcomes. Our recommendations are oriented toward the United States as the situation may differ in low-and middle-income settings.…”
Section: Neonatal Outcomesmentioning
confidence: 99%